Assessment of student weight during the social isolation of the COVID-19 pandemic (Research, Society and Development, 2022)
This study aims to verify the weight variation of high school students from a private school in Teresina-Piauí during social isolation due to the COVID-19 pandemic. This was an observational epidemiological study, through the collection of XX student forms, through which a survey of socio-demographic data was carried out. With the results of this study, it was observed that Research data suggest that the pandemic caused by Sars-Cov-2 was associated with greater increases in body weight after the pandemic than before. The spread of dietary regulation and healthy coping strategies is of critical importance during the COVID-19 pandemic to prevent weight gain and unhealthy eating patterns.